Proposal for the Development and Implementation of a Sanitary Protocol for Intra-hospital Canine Assisted Therapy - Castaño Peña, Astrid Valentina
The connection between humans and animals has strengthened over the years, and it is known that this relationship has existed for centuries. Animal-assisted interventions have been of paramount importance in the development of various psychoeducational programs and strategies. These interventions aim to provide therapeutic or educational assistance and engage in activities with adults and children facing difficulties or disorders that may impact their cognitive and learning development. In the case of dogs, it is recommended to bring the dog to the hospital in optimal hygienic conditions, presenting a healthy and clean appearance (Veterinary Journal, 2020). The lack of scientific evidence and sanitary management protocols for canines has been the main obstacle to implementing this therapy modality in hospitals in Colombia. The purpose of this study is to develop and implement a sanitary protocol from a parasitic perspective in canines. To achieve this, samples of fecal matter were obtained from the ten (10) canines previously selected by the Colombian and Bogotá Cruz Roja. These samples were analyzed to determine the presence or absence of potentially pathogenic parasites using qualitative and quantitative flotation and sedimentation techniques to identify forms compatible with parasites.